PERBANDINGAN PELATIHAN LONCAT RINTANGAN 50 CM DENGAN VARIASI LARI CEPAT 5 METER ANTARA 10 REPETISI 3 SET DAN 5 REPETISI 6 SET TERHADAP PENINGKATKAN TINGGI LONCATAN VERTIKAL PADA MAHASISWA SEMESTER II PUTRA DI FPOK IKIP PGRI BALI - Ni Luh Gde Widiantari; I D P. Sutjana; I P G. Adiatmika (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2015)
In volley ball game, the mistakes that usually conduct by athlete was inaccurate of the blocking move, therefore the hit which was conducted by the rivals always unblock. It was caused by less of good physical condition and well block technique then it was effected the jump high. The training was needed to improve the bad physical condition and block’s technique. Leg muscle explosive power is one of the important components of the physical condition which was required in sports especially in barrier’s jump. The exercise which is used in this study was exercise of barrier’s jump in 50 cm with variations of sprint 5 meters 10 repetitions 3 sets and 5 repetitions 6 sets. This training aims to compare the training which further enhances the high jump, to find out the effectiveness of barrier’s jump of 50 cm with a variation of 5 meter sprint to the increasing of jump’s high. It had been conducted the research of experimental study with randomized pre- and post- test control group design. The numbers of the samples were 28 people that were divided into two groups, the number of each group was 14 people that were chosen randomize with a simple lottery. Group 1 was given the exercise of 50 cm barrier’s jump with variation of sprint was 5 meters 10 repetitions 3 sets, and group 2 was given 50 cm barrier’s jump with the sprint’s variation was 5 meters 5 repetitions 6 sets. From the statistical test results is obtained , the average of group 1 vertikal jump’s height before training was 55.28 ± 9.46 and after training was 62.64 ± 9.70 with deference 7,07 ± 1.85 (p